2013
DOI: 10.1186/2052-4374-25-6
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth and Related Factors of Child Protective Service Workers

Abstract: ObjectivesThe aim of the study is to measure the level of vicarious trauma, posttraumatic growth (PTG), and other factors affecting PTG among child protective service workers.MethodsWe include posttraumatic stress, social support, stress coping, and demographic data as independent variables. Data was collected from 255 full-time social workers from 43 child protective agencies as acomplete enumeration and 204 included in the final analysis.ResultsThe major findings of the study were as follows: The mean score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
0
22
1
1
Order By: Relevance
“…Further, China’s traditional cultural value systems (i.e., Confucianism, Taoism) might affect thinking patterns of individuals who might form a more meaningful narrative about trauma [ 60 , 61 ]. In addition, the score was slightly higher than that reported in studies of psychiatric nurses and social workers [ 24 , 30 , 62 ]. Emergency rescues involve extremely urgent life-and-death situations, short recovery times between emergencies, and frequent exposure to trauma experienced by patients [ 27 ].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Further, China’s traditional cultural value systems (i.e., Confucianism, Taoism) might affect thinking patterns of individuals who might form a more meaningful narrative about trauma [ 60 , 61 ]. In addition, the score was slightly higher than that reported in studies of psychiatric nurses and social workers [ 24 , 30 , 62 ]. Emergency rescues involve extremely urgent life-and-death situations, short recovery times between emergencies, and frequent exposure to trauma experienced by patients [ 27 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Individuals with high levels of support have more opportunities to narrate their trauma and survival, and to adopt a perspective that can be integrated into a schema change [ 15 , 29 ]. A growing body of literature supports research findings of a positive effect of social support on PTG [ 30 - 33 ]. One investigation of cancer survivors indicated that social support helped traumatized people reinterpret their present situation, stimulate their cognitive processes, and, in turn, foster their meaning-making process [ 33 ].…”
Section: Introductionmentioning
confidence: 91%
“…Reported predictors of vicarious PTG include social support and empathy (Rhee, Ko, & Han, 2013), working with trauma victims (Brockhouse, Msetfi, Cohen, & Joseph, 2011), bonding with patients (Linley & Joseph, 2007), job satisfaction (Gibbons et al, 2011), and professional self‐esteem (Taubman‐Ben‐Ari & Weintroub, 2008). Some of these predictors were mentioned in the open‐ended question responses, where some nurses described positive changes in their lives after caring for war trauma victims.…”
Section: Discussionmentioning
confidence: 99%
“…Les travailleurs en protection de la jeunesse (PJ) sont à haut risque d'éprouver des problèmes de santé psychologique tels qu'un trouble de stress post-traumatique (TSPT; Horwitz, 2006;Rhee, Ko et Han, 2013) ou un épuisement professionnel (Anderson, 2000;Bennett, Plint et Clifford, 2005). Des études (Meadors et Lamson, 2008;Regehr, Hemsworth, Leslie, Howe et Chau, 2004) montrent que cet état de fait est partiellement attribuable à l'environnement de travail de la PJ.…”
Section: Introductionunclassified